Religion in public : Locke's political theology - Pritchard, Elizabeth A. (Elizabeth Ann) (Cultural memory in the present., 2014)
John Locke's theory of toleration is generally seen as advocating the privatization of religion. This interpretation has become conventional wisdom: secularization is widely understood as entailing the privatization of religion, and the separation of religion from power. This book turns that conventional wisdom on its head and argues that Locke secularizes religion, that is, makes it worldly, public, and political.